Impacts of pre-pregnancy exposure to per- and polyfluoroalkyl substances on menstrual characteristics among women undergoing assisted reproductive technology - Huyi TAO; Yujie CAO; Yitao PAN; Jiuru ZHAO; Zhiwei LIU; Yu GAO; Ying TIAN (环境与职业医学)
BackgroundPer- and polyfluoroalkyl substances (PFAS) are a class of persistent organic pollutants widely used in various products, leading to population exposure and long-term accumulation. At present, there is a lack of research on the relationships between pre-pregnancy PFAS and menstrual characteristics among women undergoing assisted reproductive technology (ART) in China. ObjectiveTo explore the relationships between pre-pregnancy PFAS exposure among women undergoing ART and menstrual characteristics prior to assisted reproductive treatment. MethodsThis study employed a cross-sectional research design, recruiting women undergoing ART treatment at the Reproductive Clinic of the International Peace Maternity & Child Health Hospital, School of Medicine, Shanghai Jiao Tong University, from 2017 to 2020 as study participants. Ultra-high-performance liquid chromatography-tandem mass spectrometry was used to detect 42 types of PFAS in pre-pregnancy serum samples. Questionnaires were administered to collect information on demographic characteristics, lifestyle habits, and menstrual characteristics (average menstrual cycle length, average menstrual period length, menstrual irregularities, and menstrual bleeding volume) of women undergoing ART. Multiple linear regression, binary logistic regression, and multinomial logistic regression analyses were performed to investigate the relationships between individual PFAS exposure before pregnancy and menstrual characteristics among ART women. Additionally, weighted quantile sum (WQS) model was applied to analyze the association between PFAS mixtures and menstrual characteristics. ResultsIn the pre-pregnancy serum samples of the study population, 15 PFAS were detected in more than 60% of the samples, including perfluoroheptanoic acid (PFHpA), perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), perfluoroundecanoic acid (PFUnDA), perfluorododecanoic acid (PFDoDA), perfluorobutanesulfonic acid (PFBS), perfluorohexanesulfonic acid (PFHxS), perfluoroheptanesulfonic acid (PFHpS), perfluorooctanesulfonic acid (PFOS), 6:2 chlorinated polyfluorinated ether sulfonate (6:2 Cl-PFESA), 8:2 chlorinated polyfluorinated ether sulfonate (8:2 Cl-PFESA), perfluoro-2-propoxypropanoic acid (HFPO-DA), perfluoro-2-methoxyacetic acid (PFMOAA), and perfluoro-(3,5,7,9,11-pentaoxadodecanoic) acid (PFO5DoDA). Among them, PFOA had the highest median concentration of 9.160 ng·mL−1. The single PFAS exposure analysis revealed a positive correlation between PFAS and irregular menstrual cycles. Specifically, for every natural-log unit (e) increase in PFOA, PFBS, or PFHxS level, the incidence of irregular menstrual cycles increased by 57%, 42%, or 39%, respectively. Most PFAS were positively correlated with the average number of menstrual cycle days, such as PFHpA (b=1.08, 95%CI: 0.11, 2.05), PFOA (b=1.69, 95%CI: 0.39, 3.00), PFBS (b=1.23, 95%CI: 0.25, 2.22), PFHxS (b=1.47, 95%CI: 0.61, 2.32), PFHpS (b=1.48, 95%CI: 0.35, 2.61), and 6:2 Cl-PFESA (b=0.90, 95%CI: 0.08, 1.72). Furthermore, levels of PFHpA (OR=1.39, 95%CI: 1.06, 1.82), PFOA (OR=1.58, 95%CI: 1.09, 2.30), PFBS (OR=1.37, 95%CI: 1.04, 1.80), PFHxS (OR=1.34, 95%CI: 1.05, 1.71), PFHpS (OR=1.53, 95%CI: 1.10, 2.14), and 6:2 Cl-PFESA (OR=1.34, 95%CI: 1.06, 1.70) were positively correlated with low menstrual blood volume, while PFOA (OR=0.40, 95%CI: 0.23, 0.71), PFHpS (OR=0.45, 95%CI: 0.29, 0.71), and HFPO-DA (OR=0.68, 95%CI: 0.48, 0.97) were negatively correlated with high menstrual blood volume. The mixed exposure model showed that PFAS mixtures were positively correlated with the average number of menstrual cycle days (b=1.60, 95%CI: 0.49, 2.71), irregular menstrual cycles (OR=1.77, 95%CI: 1.19, 2.63), and low menstrual blood volume (OR=1.59, 95%CI: 1.08, 2.35), but negatively correlated with high menstrual blood volume (OR=0.40, 95%CI: 0.22, 0.73). ConclusionWomen undergoing ART in Shanghai are widely exposed to PFAS prior to conception. Exposure to PFAS before pregnancy may be related to menstrual characteristics among women seeking ART before undergoing fertility treatments, but additional data from larger populations are required to validate the findings of this study.